Novel techniques in wind engineering. Issue 171 (December 2017) - Hangan, Horia; Refan, Maryam; Jubayer, Chowdhury; Romanic, Djordje; Parvu, Dan; LoTufo, Julien; Costache, Adrian
Abstract: While the Alan Davenport Wind Engineering Chain is still valid today, the wind engineering techniques and methodologies have evolved. These changes relate to methods of collecting full scale data, physical and numerical modeling techniques, analysis techniques and wind-structure interaction approaches. These methodologies allow us to look at a more diverse spectrum of wind events including non-stationary, non-synoptic winds and their impact on buildings and structures. Spatially distributed full scale data combined with mesoscale and microscale simulations are more fitted today to characterize the local climatic scales associated to these complex wind events. These wind fields are three-dimensional, non-stationary and sometimes non-Gaussian in nature. However, our well-established Boundary Layer Wind Tunnels produce straight and steady wind and are limited in Reynolds number. The development of larger, multi-fan and sometimes three-dimensional wind facilities has now enabled more realistic laboratory simulations of surface flows for these events. Also, it invites new insight in data analysis and the way we treat the wind-structure interaction problems in a non-stationary context. In view of all this, we provide a review of new emerging technologies and examples of their applicability in the context of new experiments conducted at the WindEEE Research Institute at Western. Highlights: Non-synoptic, non-stationary wind events pose new challenges to address wind structure interactions. Larger, multi-fan, three dimensional wind facilities allow the simulation of non-synoptic wind events more realistically. Novel techniques to address these wind events are reviewed through the experiments performed at the WindEEE Dome.